2012
DOI: 10.1128/mcb.05229-11
|View full text |Cite
|
Sign up to set email alerts
|

Novel Roles of Caenorhabditis elegans Heterochromatin Protein HP1 and Linker Histone in the Regulation of Innate Immune Gene Expression

Abstract: Linker histone (H1) and heterochromatin protein 1 (HP1) are essential components of heterochromatin which contribute to the transcriptional repression of genes. It has been shown that the methylation mark of vertebrate histone H1 is specifically recognized by the chromodomain of HP1. However, the exact biological role of linker histone binding to HP1 has not been determined. Here, we investigate the function of the Caenorhabditis elegans H1 variant HIS-24 and the HP1-like proteins HPL-1 and HPL-2 in the cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 63 publications
5
59
0
Order By: Relevance
“…Its Ume6-dependent recruitment to early meiotic genes supports a growing body of evidence that linker histones, although ubiquitous throughout the genome, may play specific roles in the repression of related genes via transcription factor recruitment (10,33,37,48,52). In addition, Hho1 plays a role in genome compaction specifically in the late stages of sporulation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Its Ume6-dependent recruitment to early meiotic genes supports a growing body of evidence that linker histones, although ubiquitous throughout the genome, may play specific roles in the repression of related genes via transcription factor recruitment (10,33,37,48,52). In addition, Hho1 plays a role in genome compaction specifically in the late stages of sporulation.…”
Section: Discussionmentioning
confidence: 71%
“…Alternatively, Hho1 may be phosphorylated to affect the interaction, as linker histone association to chromatin is dynamic and affected by phosphorylation in higher eukaryotes (34). Moreover, the heterochromatin protein HP1 has been shown to recruit specifically methylated H1 to the promoters of genes involved in the immune response in Caenorhabditis elegans (48). Thus, it is possible that in S. cerevisiae, posttranslational modification of Hho1 or Ume6 may alter their association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the absence of HPL-2 improves survival following the induction of acute ER stress by two distinct stressors. Importantly, increased resistance to ER stress does not reflect a general resistance to stress conditions, as hpl-2 mutants are inheritently sensitive to thermal stress (8), more sensitive to osmotic stress (10), but unaltered in their response to oxidative stress (7).…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work showed that recruitment of the hPaf1 complex to HAdV genes required hBre1 (6). The hPaf1 complex comprises 6 subunits: Cdc73, Ctr9, Leo1, hPaf1, Rtf1, and Ski8 (17)(18)(19)(20). Previous work has shown that hBre1 binds to the hPaf1 complex (16).…”
Section: Resultsmentioning
confidence: 99%